Pelatihan Peningkatan Keterampilan Survei Pemetaan dengan Global Positioning System di Sekolah Menengah Kejuruan Samarinda - Andrew Stefano; Sri Endayani; Fathiah Fathiah; Ida Rosanti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The city of Samarinda plays a vital role as the main contributor to the country's foreign exchange through the coal mining and oil palm plantation sectors. Thanks to this region's high-calorie coal content, Samarinda is often the centre of land disputes. This service activity aims to provide counselling and training regarding geographic information systems to Vocational High School (SMK) students in Samarinda. Global Positioning System (GPS) technology plays a vital role in this program, considering its ability to determine location coordinates on the Earth's surface. This training introduces Garmin GPS to students, covers its features and functions, and explores student responses to the training material. The methodology includes counselling and direct practice in the field, with students' understanding and perceptions evaluated through pre-tests and post-tests. The evaluation results show that the training program increased participants' understanding, skills and acceptance of mapping concepts. It was also noted that there was a decline in student enthusiasm and participation after the training. The geographical conditions of Samarinda, characterized by wide rivers, swamps, hills, ravines, and a fluctuating climate, add to the challenges in collecting coordinate point data. Therefore, intensive mentoring is an essential key to ensuring the sustainability and effectiveness of this program in the future.